Fuzzy Water Level Control System - Patil, Jeevan; Awati, J. S.; Kumbhar, M. S. (Journal of Electronic Design Engineering, 2023)
To precisely maintain desired water levels within specified ranges, a fuzzy logic-based water level control system is introduced in this research paper. The robustness and adaptability of fuzzy logic were used to efficiently handle dynamic shifts and disruptions. The outcomes demonstrate the accuracy of the system and its potential to improve control in a range of applications. This work advances the field of water level control by highlighting fuzzy logic's potential for increased accuracy and flexibility.